2012
DOI: 10.1186/1471-2458-12-56
|View full text |Cite
|
Sign up to set email alerts
|

Patient- and provider-level risk factors associated with default from tuberculosis treatment, South Africa, 2002: a case-control study

Abstract: BackgroundPersons who default from tuberculosis treatment are at risk for clinical deterioration and complications including worsening drug resistance and death. Our objective was to identify risk factors associated with tuberculosis (TB) treatment default in South Africa.MethodsWe conducted a national retrospective case control study to identify factors associated with treatment default using program data from 2002 and a standardized patient questionnaire. We defined default as interrupting TB treatment for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
68
3
18

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 22 publications
10
68
3
18
Order By: Relevance
“…Similar to our study, two African studies found that younger age is associated with non-adherence [20,21]. This association was also observed in the Indian and Moroccan studies [7,19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to our study, two African studies found that younger age is associated with non-adherence [20,21]. This association was also observed in the Indian and Moroccan studies [7,19].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is supported by a large case-control study conducted by Finlay et al [21] in South Africa. Other studies in Africa also show that difficulties of physical access and transfer of cases to other healthcare units related to moving of residence affected adherence to TB treatment negatively [20,24].…”
Section: Discussionsupporting
confidence: 67%
“…16 Temporal-spatial variations in the gap between incidence estimates for microbiologically confi rmed pulmonary tuberculosis and new cases registered for treatment were noted, which could be caused by both patient and provider factors. 17,18 In 2012, this gap was more than 25% in fi ve of the nine provinces, which is concerning because patients not linked to care could be the major source of persisting M tuberculosis transmission in the community. Several limitations were also noted for data for new cases registered for treatment, including some provinces lacking or only having limited data for some years.…”
Section: Discussionmentioning
confidence: 99%
“…Castelnuovo (2010) dalam kajian kualitatif yang beliau jalankan bagi melihat kepada faktor risiko cicir rawatan mendapati antara faktor yang menyebabkan cicir rawatan dalam kalangan pesakit tuberkulosis di Sub-Sahara Afrika adalah kurang pengetahuan mengenai rawatan tuberkulosis (Castelnuovo 2010). Selain itu, menggunakan reka bentuk kajian yang berbeza faktor ini turut sama dilaporkan mempunyai perkaitan beerti dengan ketidakpatuhan dalam kajian kes kawalan dalam kalangan pesakit tuberkulosis cicir rawatan di Afrika Selatan (Finlay et al 2012). Ada di antara responden dalam kajian semasa ini menyatakan yang mereka berhenti daripada mengambil ubat kerana merasakan diri sudah sihat.…”
Section: Perbincanganunclassified
“…Ada di antara responden dalam kajian semasa ini menyatakan yang mereka berhenti daripada mengambil ubat kerana merasakan diri sudah sihat. Hal yang sama turut dinyatakan di dalam kajian sebelum ini (Finlay et al 2012;Slama et al 2013).…”
Section: Perbincanganunclassified